A STUDY ON CONSUMER PREFERENCE FOR RYTHUBAZAARS IN TWIN CITIES (International Journal of Food and Nutritional Sciences, 2022)
Rythu Bazars' works on the concept of direct agricultural marketing are the most successful markets in the State of Andhra Pradesh. The consumers well received the concept of Rythu Bazar in Andhra Pradesh and Lakhs of the consumers are going to benefit from these markets in the State. Consumers feel that Rythu Bazar is the most affordable and accessiblemarket where all the vegetables and grocery items are available in one place. These markets are being run and organised by Government officials to eliminate the intermediaries and facilitate the farmers with marketing information to sell their produce directly to consumers. Due to the excellent organisation and proper price fixation of the products, Rythu bazaars are the most successful markets in the State. In this context, the present Paper deals with the consumer preference for rythu bazars based on the factors like availability, affordability, accessibility, and quality comparatively with supermarkets, street vendors and other mandies based on the survey conducted in the twin cities of Andhra Pradesh.